2014
DOI: 10.1088/0957-0233/25/8/085007
|View full text |Cite
|
Sign up to set email alerts
|

Errors in shearography measurements due to the creep of the PZT shearing actuator

Abstract: Shearography is a modern optical interferometric measurement technique. It uses interferometric properties of coherent laser light to measure deformation gradients on the µm/m level. In the most common shearography setups, the ones employing Michelson interferometer, the deformation gradients in both x-and y -direction can be identified by setting angles on the shearing mirror. One of the mechanisms for setting the desired shearing angles in the Michelson interferometer is using the PZT actuators. This paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Thus the shearography measurements are affected by the air-currents, especially the warm air rising between the camera, the laser and the observed surface. The environmental disturbances can be considered random and their influence is increased with the duration of the experiments [21]. The high-frequency noise is related to the laser speckle and the speckle decorrelation and the influence of it can be reduced by filtering.…”
Section: Errors In Shearographymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus the shearography measurements are affected by the air-currents, especially the warm air rising between the camera, the laser and the observed surface. The environmental disturbances can be considered random and their influence is increased with the duration of the experiments [21]. The high-frequency noise is related to the laser speckle and the speckle decorrelation and the influence of it can be reduced by filtering.…”
Section: Errors In Shearographymentioning
confidence: 99%
“…The PZT material can exhibit creep behaviour, which can affect the measurement. Research by our group [21] showed that the PZT creep can create a considerable error in the measurements. This error is more pronounced with increasing duration of the measurement, so it is important mostly for long time-span measurements.…”
Section: Errors In Shearographymentioning
confidence: 99%
See 2 more Smart Citations